Written sources in Tibetan language in the collections of the National Museum of the Republic of Tuva - Sumba, Rita P. (The New Research of Tuva, 2019)
Among the collections of the National Museum of the Republic of Tuva there are over 20000 archival units of manuscripts and xylographs in Tibetan language. This article examines the history of the collection, focusing on the various aspects of studying Tibetan xylographs and manuscripts. For its sources, the article relies on the museum’s acquisition books and a number of research works on the topic.The earliest items in the collection were acquired in 1954. Since then, it was expanded at irregular times, over several decades and from various sources. However, it would not be a mistake to suggest that the bulk of the collection came from the libraries of Tuva’s disbanded Buddhist monasteries.Religious and ritualistic texts, together with books of the Buddhist canon, account for up to 80% of the collection of Tibetan manuscripts and xylographs in the museum’s funds. One of them is a rare copy of the Kangyur Buddhist canon, the only one discovered in Tuva. It was made in Urga. Mongolia, in 1908-1910 and found in a cave in Kyzyl rayon – probably hidden during the anti-religious campaign of the 1930s. The copy consists of 94 volumes, categorized into 9 partitions (their titles in Tibetan and Sanskrit can be found in the article).A large part of the Tibetan collection in the National Museum belongs to relatively small canonical works from the Kangyur in numerous reduplicating volumes. A separate group is found in the textbooks used in the monasteries for studying the Buddhist tradition. Never made in Tuva proper, it had been brought over from Buryatia and Mongolia. However, the texts of religious nature, as well as those dealing with ritual and everyday practice, were published at the printing shops of the largest Tuvan khuree (monasteries). This can be seen from a collection of a carved xylographic page boards which were used as a matrix for printing. Museum collections thus can be proved to have shed a lot of light on our understanding of the development of Buddhism in Tuva.
Keywords: monument of literature; Tibetan language; National Museum of the Republic of Tuva; Tuva; Tibetan literature; xylograph; Buddhism in Tuva; Kangyur of Urga; Kangyur